ANALISIA RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN REAL ESTATE DAN PROPERTY DI BURSA EFEK INDONESIA (BEI) - Benny Hidayat; Haryetti '; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted on the property & real estate company listed on the Indonesia Stock Exchange Period 2009-2013. The purpose of this study was to determine the effect of the current ratio, net profit margin, return on equity, total asset turnover and debt to equity ratio toward the predicted change in earnings. The population in this study are all property & real estate company listed on the Indonesia Stock Exchange during the years 2009-2013 as many as 42 companies. The sampling technique by purposive sampling by certain criteria. Based on the established criteria, there are 37 companies that meet the sample’s criteria. Analysis of data using multiple regression models.These results concluded that the Return On Equity has a partially significant effect on earnings growth. Debt to Equity Ratio has an effect on earnings changes. Current Ratio does not have a significant effect on earnings growth, Net Profit Margin do not have a significant effect on earnings growth. Total Asset Turn Over then TATO has no significant effect on earnings growth.Keywords: Return on Equity (ROE), Deebti to Equity Ratio (DER), Current Ratio (CR), Net Profit Margin (NPM), Total Asset Turn Over (TATO), changes in profit